The Role of Islamic Banking in Promoting Financial Inclusion and Economic Development in Uganda - Shamim Nakamya (Uganda Christian University, 2025)
This paper examined the role of Islamic banking in promoting financial inclusion and economic development in Uganda. The fact that the concept of Islamic banking is a new one and therefore known to a few, the primary objective of the research was to assess its effectiveness in promoting financial inclusion and economic development in Uganda. The researcher adopted a doctrinal research method to analyse the existing laws and literature and found that, Islamic banking has the potential to address financial exclusion and improve access to financial services as well as boost economic development. However, despite this, its adoption has been sluggish with factors such as regulatory gaps, low awareness, misconceptions and lack of Sharia’h knowledge, hindering its development. Consequently, the study recommends that stakeholders launch public awareness campaigns about the role of Islamic banking in promoting financial inclusion and economic development.